Acknowledging ecological debt: towards just, humane and sustainable food systems in Africa - Mbaka, Mwenda; Cox, Janice H. (Frontiers in Animal Science, 2025)
This review interrogates the historical and ongoing consequences of the Global North’s industrialization trajectory on the Global South, including the industrial agriculture systems subsequently exported to the Global South. These caused significant ecological harms including major impacts on the “triple planetary crisis” of climate change, pollution and biodiversity loss – which were disproportionately caused by the Global North and disproportionately affected the Global South; and other detrimental impacts on human and animal well-being. Africa has been used as a focus for examining these issues, revealing additional harms to traditional African livestock practices and cultural values such as Ubuntu and Ukama, which emphasize interconnectedness and respect for all living beings (and accord with One Health principles). This paper considers the concept of ecological debt in this context, underscoring the moral and financial responsibility of industrialized nations to provide “restorative justice” for these multiple harms, and proposing that this should be used to support just transition toward humane, sustainable and culturally-appropriate food systems in Africa. A 3Rs framework - Reduction, Refinement, and Replacement - is proposed to guide this transition. Reduction includes addressing food waste and rebalancing diets toward plant-based options. Refinement emphasizes regenerative agriculture, animal welfare, and traditional knowledge. Replacement promotes healthy, nutritious alternatives, including indigenous superfoods, plant-based, and cultivated products. However, food systems change is complex, and barriers to change remain – particularly as regards policy, funding, quantifying and securing ecological debt, and dietary change – all of which could benefit from values-based governance, and holistic reform based on further specialist research.